2016
DOI: 10.1016/j.najef.2015.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Linking transformational leadership and core self-evaluation to job performance: The mediating role of felt accountability

Abstract: The present study examines the mediating effects of felt accountability on the relationship of both transformational leadership as well as core self-evaluation on task and contextual performance. SEM with AMOS was used to analyze the data collected from questionnaires distributed to 302 supervisor-employee dyads. The concept of felt accountability is based on a social contingency model of accountability, which is distinct from the feelings of responsibility or obligation in organizational research. Our hypothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…12,46 When employees perceive supervisor behavioral integrity at a low level, the resulting role ambiguity and role conflict will restrain employees from forming an emotional attachment. 47 In summary, Affective commitment has a mediating effect on supervisor behavioral integrity and employee proactive behavior. Based on the above discussion, this research proposed the following hypothesis: Hypothesis 2: Affective commitment mediates the relationship between supervisor behavioral integrity and employee proactive behavior.…”
Section: Mediating Role Of Affective Commitmentmentioning
confidence: 98%
“…12,46 When employees perceive supervisor behavioral integrity at a low level, the resulting role ambiguity and role conflict will restrain employees from forming an emotional attachment. 47 In summary, Affective commitment has a mediating effect on supervisor behavioral integrity and employee proactive behavior. Based on the above discussion, this research proposed the following hypothesis: Hypothesis 2: Affective commitment mediates the relationship between supervisor behavioral integrity and employee proactive behavior.…”
Section: Mediating Role Of Affective Commitmentmentioning
confidence: 98%
“…Khanin (2007) states that transformational leadership can boost the performance of the followers through charisma, intellectual encouragement, individual attention and inspiration [6]. Transformational leadership puts identification with human values to forefront.…”
Section: Sense Of Transformational Leadershipmentioning
confidence: 99%
“…This study aims to examine how the process of stimulating employee accountability is explained against the backdrop of leadership and organizational aspects. Previous studies have found various antecedents of accountability, but only a few have discussed the importance of the aspects of leadership in relation to employee accountability (Chen, et al, 2016;Steinbauer, et al, 2013). Consequently, this study considers leader humility as an aspect of leadership and perceived organizational support as an organizational aspect that affects accountability.…”
Section: Introductionmentioning
confidence: 99%
“…Extant literature on accountability have shown that it improves employees job satisfaction, enhances organizational citizenship behavior, reduces work pressure, and reduces turnover intention (Brees et al, 2020;Chen et al, 2016;Dai et al, 2018;Lanivich et al, 2010;Wallace et al, 2011;Wikhamn & Hall, 2014). Thus, a decline in employee accountability could, on the other hand, put both employees and companies against more adversity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation